2005
DOI: 10.1007/s00268-004-7482-5
|View full text |Cite
|
Sign up to set email alerts
|

Gallstone Disease after Extended (D2) Lymph Node Dissection for Gastric Cancer

Abstract: Few studies have reported the incidence and clinical outcomes of gallstone disease after extended (D2) lymph node dissection for gastric cancer. The present study was designed to retrospectively compare limited (D1) and D2 dissections in terms of gallstone formation, presentation of gallstones, and surgery for gallstone disease. A total of 805 Japanese gastric cancer patients (595 male, 210 female) who underwent curative resection with D1 (n = 490) or D2 (n = 315) dissection were retrospectively reviewed. Of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 43 publications
2
38
2
Order By: Relevance
“…No patient in the present study had symptomatic cholecystolithiasis or received treatment for gallstones. In contrast, a previous study reported that cholecystolithiasis developed in 27 % of patients with gallstones after open gastrectomy, and 46 % of these patients received surgical treatment [28]. The reconstruction method of choice after LDG remains controversial.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…No patient in the present study had symptomatic cholecystolithiasis or received treatment for gallstones. In contrast, a previous study reported that cholecystolithiasis developed in 27 % of patients with gallstones after open gastrectomy, and 46 % of these patients received surgical treatment [28]. The reconstruction method of choice after LDG remains controversial.…”
Section: Discussionmentioning
confidence: 64%
“…Total cholesterol, mean ± SD 0.91 ± 0.16 0.94 ± 0.15 0.34 in another study including patients who underwent open gastrectomy (D1 9.4 %; D2 17.8 %) [28]. Apart from the passage of food through the duodenum, destruction of the vagus nerve is also an important risk factor for gallstone formation [29] and such destruction was marked in patients who had undergone extensive lymph node dissection.…”
Section: Discussionmentioning
confidence: 99%
“…According to the inclusion and exclusion criteria, we rejected the literature which didn't fit criterion, then 15 literatures (Mizuta et al, 1990;Pezzolla et al, 1993;Kodama et al, 1995;Wu et al, 1995;Hidetoshi et al, 1998;Furukawa et al, 1999;Shibata et al, 2004;Tomita et al, 2004;Akatsu et al, 2005;Kobayashi et al, 2005;Yoo et al, 2005;Nunobe et al, 2007;Kojima et al, 2008;Fukagawa et al, 2009;Sun et al, 2011) were included into this study, including 3 RCT articles, 5 cohort study articles and 7 case-control study articles. The number of cases is from 32 to 893 in the 15 articles.…”
Section: Literature Retrievalmentioning
confidence: 99%
“…Many studies reported a three-four fold increased incidence 5 years after gastric surgery (up to 15-25 %) [1][2][3][4][5][6] with an estimated mean value of 17 % in all studies [1][2][3][4][5][6][7]. The underlying mechanism was thought to be related to surgical dissection of the vagus nerve branches and the anatomical gastrointestinal reconstruction [5,[8][9][10], and to the extent of gastrectomy and lymphadenectomy [1,4,[11][12][13].…”
Section: Introductionmentioning
confidence: 99%